Results of a national survey on knowledge and use of complementary and alternative medicine by paediatricians - Roi Piñeiro Pérez; Esmeralda Núñez Cuadros; Lourdes Cabrera García; Ignacio Díez López; Raquel Escrig Fernández; María Ángeles Gil Lemus; Santiago Manzano Blanco; Belén Rodríguez Marrodán; Cristina Calvo (Elsevier, 2022)
Introduction: The use of certain Complementary and Alternative Medicines (CAM) in children has been documented in Spain. The main aim of this study is to estimate the knowledge, recommendations, and use of CAM by Spanish paediatricians. Material and methods: A national study was conducted from June to July 2020 using an online questionnaire. Two e-mails were sent to paediatricians who were members of the Spanish Association of Paediatrics (AEP). Results: Out of 1414 responses received, acupuncture was considered as a science by 31.8%. Homeopathy was recommended to parents by 28.1%. CAM was used by 21.3% of physicians, at least once, to improve their own health. Only 3.8% had ever replaced a conventional treatment with CAM. The following variables were associated with a greater disposition to prescribe homeopathy: female, age over 45 years old, paediatricians working in Primary Care, and paediatricians working in private healthcare. Conclusions: This AEP Committee on Medicines questionnaire provides new data that should be considered alarming and should ask for a serious thinking on the use of CAM in Spain. Some paediatricians are recommending parents to give treatments not supported by scientific evidence to their children. This practice could be potentially harmful, especially when conventional treatment is being replaced. Resumen: Introducción: El uso de determinadas pseudociencias en niños está documentado en España. El objetivo principal del estudio es estimar el grado de conocimiento, la recomendación y el uso de algunas pseudoterapias por parte de los pediatras españoles. Material y métodos: Estudio transversal, descriptivo y de ámbito nacional, mediante encuesta en línea, enviada por correo electrónico a pediatras socios de la Asociación Española de Pediatría (AEP), entre junio y julio de 2020. Resultados: Se recibieron 1.414 respuestas. El 31,8% considera que la acupuntura es una ciencia. El 28,1% ha recomendado alguna vez homeopatía a sus pacientes. Un 21,3% reconoce haber utilizado alguna medicina alternativa para mejorar su propia salud. El 3,8% reconoce haber sustituido un tratamiento convencional por una terapia alternativa. Las variables que se asociaron a una mayor predisposición para recomendar homeopatía fueron: sexo femenino, edad > 45 años, trabajo en atención primaria y en un sistema de salud privado. Conclusiones: El Comité de Medicamentos de la AEP aporta con esta encuesta nuevos datos que se consideran preocupantes y que merecen una seria reflexión sobre el uso de las pseudociencias en nuestro país. Un significativo porcentaje de pediatras están recomendando a los padres que administren a sus hijos tratamientos no avalados por la evidencia científica, con todas las consecuencias negativas y perjuicios que esto puede conllevar, sobre todo si se sustituye el tratamiento convencional.